MRI ultrasound fusion biopsy in prostate cancer detection: Are randomized clinical trials reproducible in everyday clinical practice?. Issue 1 (February 2019) - Cattarino, Susanna; Forte, Valerio; Salciccia, Stefano; Drudi, Francesco Maria; Cantisani, Valerio; Sciarra, Alessandro; Fasulo, Andrea; Ciccariello, Mauro
Introduction: The aim of this study was to evaluate the performance of multiparametric magnetic resonance imaging (mpMRI)–ultrasound (US) fusion-targeted biopsies (TB) in men with primary and repeated biopsies comparing the cancer detection rate (CDR) of random biopsies (RB) + TB versus only TB. Methods: The present study is a real-life study on patients with primary and prior negative prostate biopsies with suspicious PCa. A total of 130 men with prostate-specific antigen (PSA) value >2.5 ng/dL and/or abnormal digital rectal examination (DRE) were included in the study and subjected to mpMRI. Patients with >2 previous biopsies and/or with ⩾3 suspected lesions on MRI and/or prostate imaging-reporting and data system (PIRADS) value ⩾4 (n:30 pts) were subjected only to TB on the areas indicated by mpMRI. All the other patients (n:70 pts) were subjected to standard random laterally directed 10-core plus TB on the areas indicated by mpMRI. Results: The overall CDR was 53% (53/100). In relation to PIRADS score, the overall CDR was 0, 40% (12/30), 56.83% (29/51), and 84% (11/13) for PIRADS 2, 3, 4, and 5, respectively. According to biopsy modality, CDR for RB + TB was 50% (35/70) and CDR for TB was 60% (18/30) with a p -value of 0.3632. Discussion: MRI–US fusion biopsy is associated with a high CDR of clinically significant PCa (csPCa). MRI–US fusion biopsy could be a reasonable approach in patients with previous negative biopsy and high PIRADS score on MRI, to ensure a high CDR of csPCa and to reduce the diagnosis of clinically insignificant tumors.